ANALISIS RESPON TANTANGAN YANG DIHADAPI PENGAJAR TERHADAP E-LEARNING DI POLITEKNIK PELAYARAN SORONG - LILIK YULIANINGSIH; ARIZAL HENDRIAWAN; ARIANDY SYAMSUL BHAHRI; MUHAMMAD RISYAL (JPB : Jurnal Patria Bahari, 2021)
This Research Focused On The Findings Of The Questions On The Problem Research, Namely "What Are The Challenges Faced By The Teacher Toward E-Learning?". This Research Used The Social Constructivism Pattern Model (The Social Constructivism Paradigm) As A Qualitative Research Framework To Interpret The Issues Related To This Research (Crotty, 1998). Then, The Researcher Used The Question-List Model (Questionnaire) As A Tool For Data Collection, As Suggested By Sugiyono (2010). Therefore, Data Analysis That Used In This Study Is By Reducing Data (Data Reduction), Displaying Data (Data Display), And Concluding, As Suggested By Miles & Huberman (1994). Therefore, Researchers Provided Several Solutions To Overcome The Difficulties Faced By Teachers As Challenges To E-Learning In The Discussion And Conclusions Of This Research.